Gold Complexes for Therapeutic Purposes: an Updated Patent Review (2010-2015) - Nardon, Chiara; Pettenuzzo, Nicolò; Fregona, Dolores (Current Medicinal Chemistry, 2016)
Gold has always aroused great interest in the history of mankind. It has been used for thousands of years for jewelry, religious cult valuables, durable goods and in the art world. However, few know that such a precious and noble metal was exploited in the past by the ancients also for its therapeutic properties. More recently, in the twentieth century some complexes containing gold centers in the oxidation state +1 were studied for the treatment of the rheumatoid arthritis and the orally-administered drug Auranofin was approved by the FDA in 1985. From the chemical point of view, gold derivatives deserve special attention due to the unique position of this metal within the periodic table, which results in unconventional relativistic effects and, ultimately, in the highest electronegativity, electron affinity and redox potential among all metals. In this review, after an introduction concerning the use of gold complexes in medicine, we have examined all the patents internationally or nationally published in the years 2010-2015 (until December 31, 2015) and describing new inorganic compounds containing gold(I) and gold(III) with proved therapeutic properties. These patents were filed to mainly protect compounds with promising anticancer and anti-inflammatory activities (total 18 and 4, respectively). In particular, this work explores both coordination compounds containing ligands with various donor atoms (e.g., N-, O-, S- and -P) and organo-gold derivatives with at least one Au-C bond. The toxicological profile and the intracellular targets reported for some among the patented gold derivatives are discussed.
Keywords: Auranofin